Overexpression of Human SNX27 Enhances Learning and Memory Through Modulating Synaptic Plasticity in Mice - Huo, Yuanhui; Gao, Yue; Zheng, Qiuyang; Zhao, Dongdong; Guo, Tiantian; Zhang, Shuo; Zeng, Yuzhe; Cheng, Yiyun; Gu, Huaping; Zhang, Lishan; Zhu, Bin; Luo, Hong; et al. (Frontiers in Cell and Developmental Biology, 2020)
Abnormal synaptic transmission leads to learning and memory disorders and is the main feature of neurological diseases. Sorting nexin 27 (SNX27) is an endosomal adaptor protein associated with a variety of nervous system diseases, and it is mainly responsible for the trafficking of postsynaptic membrane receptors. However, the roles of SNX27 in regulating synaptic and cognitive function are not fully understood. Here, we first generated a neuron-specific human-SNX27 transgenic mouse model (hSNX27 Tg) that exhibited enhanced excitatory synaptic transmission and long-term potentiation (LTP). In addition, we found that the hSNX27 Tg mice displayed enhanced learning and memory, lower-level anxiety-like behavior, and increased social interaction. Furthermore, we found that SNX27 overexpression upregulated the expression of glutamate receptors in the cortex and hippocampus of hSNX27 Tg mice. Together, these results indicate that SNX27 overexpression promotes synaptic function and cognition through modulating glutamate receptors.